Are China’s “Sea Turtles” Becoming “Seaweed”? A Changing Job Market - Zweig, David; Du, Zaichao (International Higher Education, 2021)
Analysts of China’s “reverse migration” largely ignore returning, short-term MA students, who comprise close to 70 percent of all returnees, seeing them as less significant. Drawing on surveys of the past 15 years, this article makes four points: The share of returned MAs in the domestic job market is huge; MAs who plan their overseas sojourn well, succeed after coming home; returning because of “family” issues is problematic; and a 20 percent “wage premium” for an overseas MA persists.